Interaction of Sex and Diabetes on Outcome After Ischemic Stroke - Soriano-Reixach, Maria Montserrat; Vivanco-Hidalgo, Rosa María; Ois, Angel; Rodríguez-Campello, Ana; Roquer, Jaume (Frontiers in Neurology, 2018)
Background: The relationship between ischemic stroke (IS), diabetes mellitus (DM), and sex is intriguing. The aim of this study was to assess the effect modification of sex in the association between DM and short- and long-term disability and mortality in first-ever IS patients. Methods: In a retrospective, observational, hospital-based study of a prospective series including first-ever IS patients from January 2006 until July 2011, differences in 3-month and 5-year mortality and disability between diabetic and non-diabetic patients (modified Rankin Scale [mRS] from 3 to 5) were analyzed by sex. Results: In total, 933 patients (36.3% with DM, 50.5% women) were included. Overall 3-month and 5-year mortality were 150 (16.1%) and 407 (44.1%), respectively. Adjusted for age, previous mRS, and stroke severity, patients with DM had significantly higher 3-month disability (HR= 1.49 [95% CI 1.39-1.70], p<0.0001), 5-year disability (HR= 1.41 [95% CI 1.07-1.86], p=0.015) and 5-year mortality (HR= 1.48, [95% CI 1.20-1.81], p<0.0001), compared to the non-DM group. Compared to non-DM women, women with diabetes had worse 3-month disability (HR: 1.81 [95% CI 1.33-2.46], p<0.0001) and 5-year mortality (HR: 1.72 [95% CI 1.30-2.20], p<0.0001), and a trend for 5-year disability (HR: 1.40 [95% CI 0.99-2.09], p=0.057). In men, DM had an effect on 3-month disability (HR: 1.45 [95% CI 1.07-1.96], p=0.018), a trend for 5-year disability (HR: 1.43, [95% CI 0.94-2.19] p=0.096), but no clear effect on 5-year mortality (HR: 1.22, [95% CI 0.91-1.65] p=0.186). Conclusions: Sex has a modifier effect on mortality in first-ever IS diabetic patients. Long-term mortality is increased in diabetic women compared with non-diabetic women, a difference not observed in men.